Crohn's disease manifesting as ileo-urachal fistula: Two cases reports and review of literatures. (2018) - Kuroki, Hirosuke; Sugita, Akira; Koganei, Kazutaka; Tatsumi, Kenji; Futatsuki, Ryo; Obara, Nao; Arai, Katsuhiko; Fukushima, Tsuneo
Highlights: Urachal tumor or umbilical discharge in Crohn's disease are examined for internal fistula from diseased ileum to urachus. En broc resection with intestinal lesion and urachus is performed with successful outcome. Partial cystectomy is sometimes performed with urinary bladder inflamed. Abstract: Introduction: A fistula involving a patent urachus in a patient with Crohn's disease is rare. Here we report ileourachal fistula formation in two patients with Crohn' disease. Case presentations: The first patient was a 29-year-old man with Crohn's disease and ileitis, and the second patient was a 43-year-old man with Crohn's disease and ileitis. One of the patients showed pus/fecal discharge via the umbilicus. Both patients were eventually diagnosed with an ileourachal fistula associated with Crohn's disease. In the first patient, the urachal remnant was connected to the urinary bladder and a Crohn's disease-related intestinal lesion had formed a fistula to the urachus. In the second patient, a periumbilical inflammatory lesion extended to the bladder through the urachal remnant and to a longitudinal ulcer of the ileal lesion. The first patients underwent partial ileal resection, and partial cystectomy, while the second patient underwent urachal curettage, partial ileal resection, and partial cystectomy. In both. Conclusion: In cases of Crohn's disease with an enterocutaneous fistula or pus discharge via the umbilicus, an examination to detect an urachal remnant with a fistula from the diseased intestine should be performed.